Cross-correlation relationship analysis of trade marks independent valuation alternative results relative errors - Pozdnyakov, Yuri V.; Lapishko, Maria L. (Journal of the Belarusian State University. Economics, 2020)
The article behaves to the field of property rights valuation on intangible assets intellectual property objects, such as trademarks (brands). An objective quantitative index ‒ relative error ‒ is applied as the criterion of valuation results uncertainty degree. Authors’ offers to execute valuation results uncertainty degree calculation based on most valuable worldwide brands rating lists, which are got from two alternative open sources. A concrete example of the most expensive world trademarks value indexes relative errors determination is shown. The main statistical characteristics of errors ranges are obtained; brands valuation results and its relative errors statistical correlation relationship quantitative determination is researched; cross-correlation coefficients of this relationship are defined. It is established that the mostly used value-in-time function models do not take into account possibility of brands value increase, i. e. negative depreciation presence. Research results are the objective confirmation of the fact, that nowadays methodical base of independent valuation is not able to provide the higher level of this class evaluation objects accuracy results. It does not depend only from an individual appraiser or concrete evaluation company. Methodology is described gives an opportunity to get the quantitative estimations of evaluation works result accuracy by relative errors estimates. Interpretation of these results is executed. Future investigations in this direction may deals with the consideration and analysis of alternative methodological errors functional relationship. The quantitative indexes of above-mentioned methodological errors relationship may be analytically determined and analyzed in detail in future researches with more than two independent sources. The importance of those researches for the further development of the information and metrological paradigm of the independent valuation methodology also is considered.